A reanalysis of nanoparticle tumor delivery using classical pharmacokinetic metrics - Price, Lauren S. L. (Sci Adv, 2020)
Nanoparticle (NP) delivery to solid tumors has recently been questioned. To better understand the magnitude of NP tumor delivery, we reanalyzed published murine NP tumor pharmacokinetic (PK) data used in the Wilhelm et al. study. Studies included in their analysis reporting matched tumor and blood concentration versus time data were evaluated using classical PK endpoints and compared to the unestablished percent injected dose (%ID) in tumor metric from the Wilhelm et al. study. The %ID in tumor was poorly correlated with standard PK metrics that describe NP tumor delivery (AUC(tumor)/AUC(blood) ratio) and only moderately associated with maximal tumor concentration. The relative tumor delivery of NPs was ~100-fold greater as assessed by the standard AUC(tumor)/AUC(blood) ratio than by %ID in tumor. These results strongly suggest that PK metrics and calculations can influence the interpretation of NP tumor delivery and stress the need to properly validate novel PK metrics against traditional approaches.